Sikap Mahasiswa Geografi UNIMA terhadap Penerapan Aplikasi Google Classroom pada Proses Pembelajaran Daring - Taliawo, Priskila; Kumaat, Joyce Christian; Lobja, Xaverius Erick; Oroh, Hilda Vemy (Jurnal Social Science, 2024)
This study aims to identify students’ attitudes towards implementing Google Classroom in the learning process. The study used quantitative research. The results showed that 68.11% of UNIMA Geography students have access to computers and smartphones for online learning, with 68.87% considering Google Classroom useful for easy announcements of materials and assignments. However, 66.28% faced obstacles such as network access and quota. Supporting factors for Google Classroom include ease of access via a browser. The overall attitude towards online learning using Google Classroom was considered good, with a score of 67.03%.